PENGARUH KOMPOSISI MEDIA TANAM DAN DOSIS PUPUK MAJEMUK TERHADAP TANAMAN SAWI HIJAU (Brassica rapa L.) - Tyas Soemarah Kurnia Dewi; Teguh Supriyadi; Endang Suprapti; Agus Budiyono; Wiyono; Joko Setiono (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2021)
The part of the mustard plant consumed is the young leaves. This research aims to determine the composition of the media and the best dose of compound fertilizer that can increase the yield of mustard greens. The method used in this research was factorial with the basic pattern of Completely Randomized Group Design with two treatments and 3 replications. The first factor is the composition of planting media: soil: sand: manure (M) which consists of three levels: M1 = 1 : 1 : 1, M2 = 1 : 1 : 2, M3 = 1 : 1: 3. While the second factor is Compound fertilizer dosage (D): D0: No fertilizer, D1: 1 g/polybag, D2: 2 g/polybag, D3 : 3 g/polybag. It will be held in February – May 2021, in the village of Bejen, Karanganyar. The treatment composition of planting media and various doses of compound fertilizer significantly affected plant height, dry stover weight, root volume and had a very significant effect on the number of leaves, fresh stover weight, plant weight, and consumption weight per plant. The highest consumption weight was 126.34 g/plant, obtained from the composition of the growing media: soil: sand: manure = 1: 1: 3, and the dose of compound fertilizer was 3 g/polybag. The lowest consumption weight was 87.07 g/plant, the composition of the soil medium: sand: manure = 1: 1: 1 and without compound fertilizer application.